Problem Based Learning Methode : Exploration related to Mathematical Connection and Problem Solving - Ningsih, Rustini; Hidayat, Wahyu; Ilmi Hidayati, Nurul (International Journal of Progressive Mathematics Education, 2024)
Abstract: The Problem-Based Learning (PBL) method has garnered significant attention as an approach to enhance students’ critical thinking and problem-solving skills, particularly in mathematics education. This research explores the impact of PBL on mathematical connection and problem-solving abilities, aiming to provide a deeper understanding of how this teaching method can foster student engagement and improve learning outcomes. The study employs a qualitative research design, utilizing case studies and observations to gather data from a sample of high school students engaged in a PBL-based mathematics curriculum. Data were analyzed using thematic analysis, identifying key themes related to students' mathematical connections and problem-solving strategies. The results suggest that PBL not only strengthens students' ability to connect mathematical concepts but also enhances their approach to solving complex mathematical problems. The research contributes to the growing body of literature on PBL by highlighting its effectiveness in promoting both conceptual understanding and practical problem-solving skills. This study offers valuable insights for educators seeking to implement PBL in mathematics classrooms, emphasizing its potential to improve student engagement, motivation, and achievement in mathematical learning.